Penerapan Business Model Madrasah Aliyah Negeri 5 Kalimantan Selatan dengan IOT - Syafie Syafie (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Currently internet of things technology has developed rapidly, where almost all fields use it. One of them is the field of education, where this field utilizes internet of things technology in the teaching and learning process. During the Covid-19 pandemic, the use of the Internet of Things is very useful in the field of education. The use of this technology makes it easier for educators and students to want to explore aspects of the benefits, for example in monitoring teaching and learning activities in the classroom, educators will get information about student activities. Student attendance is directly entered into the student and educator attendance system. The problem with education at the time of the current Covid-19 pandemic, many madrasas or schools are not ready to face the pandemic. Researchers will provide an overview of the architectural model regarding the education business model using the internet of things. Where education business architecture will be discussed regarding business architecture, information architecture and technology architecture. The purpose of implementing this business model is to plan a business model based on the Internet of Things, where urgency is needed in carrying out the teaching and learning process by utilizing the Internet of Things.